Erythrocyte sedimentation rate in new cases of pulmonary tuberculosis patients - Marlina Wijayanthy; Susanti Ratunanda (ACTA Medical Health Sciences, 2024)
This study focuses on the significant health issue of tuberculosis (TB), with Indonesia ranking as the second-highest country worldwide in TB incidence. Diagnostic advancements, including the Rapid Molecular Test (RMT), such as GeneXpert MTB/RIF Ultra, have been pivotal in identifying TB cases. In pulmonary tuberculosis, the Erythrocyte Sedimentation Rate (ESR) reveals an inflammatory process marked by elevated fibrinogen and plasma globulin levels linked to acute-phase reactions. This research, conducted at Waled Regional General Hospital, employs a quantitative descriptive approach with purposive sampling. Data on patient characteristics, new pulmonary TB cases, and ESR results are extracted from medical records, covering the period from January to June 2023. Among the 66 patients who meet the inclusion criteria, the majority (74.2%) belong to the adult age group, with males comprising 68.2%. ESR elevation is observed in 87.9% of cases, averaging 78.3 mm/hour, ranging from 5 to >140 mm/hour. ESR increase is prominent in adult males (83.7%), possibly linked to their higher daily activity and social interactions, enhancing exposure to Mycobacterium tuberculosis. Furthermore, ESR elevation in adult males may be attributed to a higher likelihood of smoking and alcohol consumption, potentially diminishing macrophage, CD4+, CD8+, and T cell activities and consequently intensifying inflammatory processes. This research sheds light on the prevalence and factors contributing to pulmonary tuberculosis, providing valuable insights for targeted interventions and public health strategies. DOI : 10.35990/amhs.v3n1.p24-30 REFERENCES Kementerian Kesehatan Republik Indonesia. Tatalaksana Tuberkulosis: Pedoman Nasional Pelayanan Kedokteran. Jakarta; 2020. Dinas Kesehatan Jawa Barat. Jumlah Kasus Penyakit Tuberkulosis Berdasarkan Kabupaten/Kota di Jawa Barat [Internet]. 2021 [cited 2023 Oct 5]. Available from: https://opendata.jabarprov.go.id/id/dataset/jumlah-kasus-penyakit-tuberkulosis-berdasarkan-kabupatenkota-di-jawa-barat Silvia H, Mellysa R, Citra T. Perbandingan nilai laju endap darah (LED) antara metode Westergren dengan metode mikro ESR pada penderita tuberkulosis paru. Jurnal Medikes. 2018;5(2):182. Sulochana S, Gayathri, Siddartha JR, Fathima J. Clinical significance of erythrocyte sedimentation rate in tuberculosis. Res J Pharm Technol. 2022;15(1):245–9. Kasih KN, Sulastina NA. Analisis laju endap darah pada pasien tuberkulosis paru. J 'Aisyiyah Medika. 2019;4:44–52. Pratiwi CD, Puspitasari E, Nurohmah V. Deskripsi jumlah leukosit dan laju endap darah pada pasien tuberkulosis di RS Paru Dungus Madiun. Borneo J Med Lab Technol. 2019;2(1):92–6. Kementerian Kesehatan Republik Indonesia. Kebijakan Program Nasional Penganggulangan TB dalam Penggunaan TCM: Petunjuk Teknis Pemeriksaan TB Menggunakan Tes Cepat Molekul. Novianti, Simarmata OS, Lolong DS. Pemanfaatan Tes Cepat Molekuler (TCM) sebagai alat diagnostik TB paru di RSUD Wangaya Kota Denpasar. Jurnal Kesehatan. 2019;18(3):135–48. Atherton RR, Cresswell FV, Ellis J, Kitaka SB, Boulware DR. Xpert MTB/RIF Ultra for tuberculosis testing in children: a mini-review and commentary. Front Pediatr. 2019;7:1–7. Sava C, Sava M, Drăgan AM, Iuhas A, Niulaș L, Marinău CP, et al. The use of Xpert MTB/RIF Ultra testing for early diagnosis of tuberculosis: A retrospective study from a single-center database. J Clin Tuberc Other Mycobact Dis. Kementerian Kesehatan Republik Indonesia. Petunjuk Teknis Tatalaksana Tuberkulosis Anak dan Remaja Indonesia. Kementerian Kesehatan Republik Indonesia. Pedoman Nasional Pelayanan Kedokteran: Tatalaksana Tuberkulosis. Zaporojan N, Negrean RA, Hodișan R, Zaporojan C, Csep A, Zaha DC. Evolution of laboratory diagnosis of tuberculosis. J Clin Med. Kementerian Kesehatan Republik Indonesia. Laporan Program Penanggulangan Tuberkulosis Tahun 2022. Listiyowati T, Wardani D, Sudarsono TA, Wijayanti L. Relationship between result of GeneXpert RT-PCR and erythrocyte sedimentation rate in suspected tuberculosis patients. J Ilmu dan Teknologi Kesehatan. 2023;10(2):259–67. Kumar A, Dutta A, Prasad A, Jain M. Survey of changes in the erythrocyte sedimentation rate at different stages of therapy by Westergren method in pulmonary tuberculosis patients in Malwa region, India. Int J Physiol. 2019;7:1–5. Ningrum WL. Profil laju endap darah pada pasien tuberkulosis kasus baru di RSU Kota Tangerang Selatan. [Skripsi]. Jakarta: Universitas Islam Negeri Syarif Hidayatullah; 2017. Bashir AB, et al. Reactive thrombocytosis and erythrocyte sedimentation rate in patients with pulmonary tuberculosis. J Med Lab Diagn. 2014;5(3):29–34. Martins C, Gama AC, Valcarenghi D, Batschauer A. Markers of acute-phase response in the treatment of pulmonary tuberculosis. J Bras Patol Lab. 2014;50:428–33. Alende-Castro V, Alonso-Sampedro M, Vazquez-Temprano N, Tuñez C, Rey D, García-Iglesias C, et al. Factors influencing erythrocyte sedimentation rate in adults: new evidence for an old test. BMC Med.